INCREASING STUDENTS' LEARNING MOTIVATION THROUGH DIRECT LEARNING STRATEGIES IN ISLAMIC RELIGIOUS EDUCATION - Hasrian Rudi Setiawan (Proceeding International Seminar of Islamic Studies, 2021)
This study aims to determine the increase in student motivation and learning outcomes through direct learning strategies in Islamic religious education at SMP PAB 1 Klumpang. This research is a classroom action research of 40 people, which is carried out with steps, namely planning, implementing, observing and reflecting. Data collection techniques through tests, observations, questionnaires and documentation. The technique of data analysis is done by reducing data, presenting data and drawing conclusions/verification. While the technique of guaranteeing the validity of the data is carried out by increasing persistence, triangulation and checking of members, discussions with colleagues, and extension of observations. The result of this research is that the students' learning motivation in SMP PAB I Klumpang has increased after using direct learning strategies, namely in the first cycle the increase in student motivation reaches 82.38% while the increase in student motivation in the second cycle reaches 86.23%. Keywords: Learning Motivation, Students, Direct Learning Strategy